Implementasi Analytic Network Process untuk Penentuan Tempat Pembuangan Akhir - Yudi Eko Windarto; Ike Pertiwi Windasari; Oki Winarto (Jurnal Komputer Terapan, 2020)
The development of life style has a negative impact that the more waste generated every day, no exception conditions in Pemalang city therefore it is necessary to focusing in the processing of waste good and efficient waste in landfill. The process of choosing landfill location is one of the important aspects and many things to be aware of. To get an objective and accurate decision is now required the processing of computerized data with modern methods using a decision support system. The method used in this system is the Analytic Network Process or abbreviated ANP. This method will be implemented on the data processing to determine the best end disposal area in a region and will be displayed visually using the map Carto. With the existence of this system will give results of ranking and overview of the best area to be built a landfill in the area. The system is built using the PHP programming language and SQL database.